Uji Efektivitas Pupuk Kompos Program CSR PT MIFA Bersaudara Terhadap Pertumbuhan Dan Hasil Tanaman Kangkung Darat (Ipeomea Reptans Poir) - Teuku Masrizal; nana ariska; Muhammad Afrillah (Jurnal Agrotek Lestari, 2022)
The CSR program which is based on Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies has done a lot of research, one of which is testing compost fertilizer on the growth and yield of land spinach. Kangkung land (Ipomoea reptans Poir) is a type of vegetable that is already known by all levels of Indonesian society, water spinach is a short-lived plant, which contains quite high nutrients. The experimental design that will be used in this study is a 4 x 1 non-factorial randomized block design (RAK), with 3 replications, so there are 12 treatment combinations. The factors to be investigated are: The effect of compost fertilizer (K) consists of 4 levels, namely: Control K0 (without fertilizer) K1 3kg/block (1kg/polybag) K2 4kg/block (1.3kg/polybag) K3 5kg/block ( 1.6 kg/polybag). Parameters observed were plant height, number of leaves (strands), number of petioles, and stem length. the results showed that the best plant height was found in the K3 treatment. on the number of leaves, the highest value was found in the K3 treatment, namely compost 5kg/block (1.6kg/polybag) treatment (K3) which was significantly different from K0 and K1 treatments, but not significantly different from (K2). on the leaf length parameter the best value was found in the K3 treatment which was significantly different from K0 (control), but not significantly different from the K1, and K2 treatments. , (strands) and the highest leaf length were found in the K3 5kg/block (1.6kg/polybag) treatment which was significantly different from the other treatments.Keywords: compost, CSR program, land kale